Analysis of Financial Performance on UMKM Tenun Ikat Troso Jepara - Hadi Ismanto (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2016)
Abstract: Analysis of Financial Performance on UMKM Tenun Ikat Troso Jepara. Indonesian Small and Medium-Sized-Enterprises give a contribution to GDP of 7% of total GDP in 2012. One factor to improve financial performance is to applicate some perspectives in the balanced scorecard concept through management capabilities, business strategy, and market orientation. The population in this study were 314 businesses, the sampling technique used purposive sampling with criteria that meet on UMKM’s subject by the Law Number 20 of 2008. Data were analyzed using multiple regression analysis. The results show that the factor of management capabilities, business strategy and market orientation has the coefficient of determination of 54.5% (R2) to the improvement of financial performance. In Partial each independent variable has a positive and significant impact on the dependent variable in this study.Keywords: Management Capabilities, Business Strategy and Market Orientation, UMKM’s Financial PerformanceAbstrak: Analisis kinerja keuangan UMKM Tenun Ikat Troso Jepara. Kontribusi UMKM terhadap PDB Indonesia sebesar 7% dari total PDB pada tahun 2012. Salah satu faktor untuk meningkatkan kinerja keuangan yaitu dengan menginterpretasi perspektif yang ada dalam konsep balanced scorecard melalui kemampuan manajemen, strategi bisnis dan orientasi pasar. Populasi dalam penelitian ini adalah 314 pelaku usaha, teknik pengambilan sampel menggunakan purposive sampling sesuai kriteria UU No. 20 tahun 2008. Data penelitian dianalisis menggunakan analisis regresi berganda. Hasil penelitian menunjukkan bahwa faktor kemampuan manajemen, strategi bisnis dan orientasi pasar memiliki nilai koefisien determinasi (R2) sebesar 54,5% terhadap peningkatan kinerja keuangan. Secara parsial masing-masing variabel bebas memiliki pengaruh positif dan signifikan terhadap variabel terikat dalam penelitian ini.Kata Kunci: Kemampuan Manajemen, Strategi Bisnis, Orientasi Pasar, Kinerja keuangan UMKM